2016
DOI: 10.1007/s10680-016-9379-z
|View full text |Cite
|
Sign up to set email alerts
|

Like Mother(-in-Law) Like Daughter? Influence of the Older Generation’s Fertility Behaviours on Women’s Desired Family Size in Bihar, India

Abstract: This paper investigates the associations between preferred family size of women in rural Bihar, India and the fertility behaviours of their mother and mother-in-law. Scheduled interviews of 440 pairs of married women aged 16–34 years and their mothers-in-law were conducted in 2011. Preferred family size is first measured by Coombs scale, allowing us to capture latent desired number of children and then categorized into three categories (low, medium and high). Women’s preferred family size is estimated using or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 81 publications
3
25
0
Order By: Relevance
“…The planned number of children by the future mothers increases with their mothers' educational level. The results support the findings of Dimitrov 10 and Taneva 9 about mother's education influence on daughters' family plans but contradict the results of Kumar et al 12 according to which the higher the education of the biological mother, the lower the size of family that the woman would like to have is. These differences in the literature on the same issue indicate that the problem should be investigated in the light of the cultural, ethnical and socio-economic environment of the family transition of fertility models and behaviour.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The planned number of children by the future mothers increases with their mothers' educational level. The results support the findings of Dimitrov 10 and Taneva 9 about mother's education influence on daughters' family plans but contradict the results of Kumar et al 12 according to which the higher the education of the biological mother, the lower the size of family that the woman would like to have is. These differences in the literature on the same issue indicate that the problem should be investigated in the light of the cultural, ethnical and socio-economic environment of the family transition of fertility models and behaviour.…”
Section: Discussionsupporting
confidence: 74%
“…We found few studies dealing with mothers' realized plans as a factor in their daughters' family planning. [9][10][11][12][13] The study of the influence of mothers' reproductive behavior on their daughters' reproductive attitude is of an undisputed interest which provoked the present study.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, the continuity of such transmission across generation may influence the fertility rate (Kumar et al, 2016;Murphy & Knudsen, 2002;Testa et al, 2016). Thus, the government should pay more attention toward the implementation of a family planning program, particularly in promoting the benefit of smaller number of children with the extent to change perception, attitude and reproductive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Number of siblings has been found to have a significant and positive effect on fertility intention where women born in a large family tend to have the same family size as their parents (Kotte & Ludwig, 2011;Murphy & Knudsen, 2002;Murphy & Wang, 2001). However, a study by Kumar, Bordone and Muttarak (2016) as well as Testa et al (2016) found that daughter's family size preferences are not associated with mother's My Mother, My Role Model: Mother's Influence on Women's Fertility Intention in Indonesia fertility but rather with the mother's level of education attainment. In this study, number of siblings is expected to be positively associated with womens' childbearing intention which indicate that family norms is transmitted from their mothers.…”
Section: Fertility Intention and Fertility Behaviourmentioning
confidence: 99%
See 1 more Smart Citation